Is the microcosm approach using meiofauna community descriptors a suitable tool for ecotoxicological studies? - Chaaban Santos, Anna Carolina; Choueri, Rodrigo Brasil; Eufrasio Pauly, Guacira de Figueiredo [UNESP]; Abessa, Denis [UNESP]; Gallucci, Fabiane (Elsevier B.V., 2018)
The usual approaches used in ecological risk assessment have been based on individual and population level standard procedures. Although these have been important tools to assess adverse effects on ecosystems, they are generally simplified and therefore lack ecological realism. Microcosm studies using meiobenthic communities offer a good compromise between the complexity of the ecosystem and the often highly artificial settings of laboratory experiments. An experiment was designed to investigate the potential of the microcosm approach using meiofauna as a tool for ecotoxicological studies. The experiment tested the ecological effects of exposure to sewage-impacted pore water simultaneously at the community level using meiofauna microcosms and at the individual level using laboratory fecundity tests with the copepod Nitokra sp. Specifically, the experiment tested the toxicity of pore water from three sites according to a contamination gradient. Both approaches were efficient in detecting differences in toxicity between the less and more contaminated sites. However, only multivariate data from community analysis detected differences in the gradient of contamination. In addition to information about toxicity, the community level microcosm experiment gave indications about sensitive and tolerant species, indirect ecological effects, as well as raised hypothesis about contamination routes and bioavailability to be tested. Considering the importance of meiofauna for benthic ecosystems, the microcosm approach using natural meiobenthic communities might be a valuable addition as a higher tier approach in ecological risk assessment, providing highly relevant ecological information on the toxicity of contaminated sediments.
Keywords: Meiofauna; Microcosm; Community assessment; Benthos; Sediment toxicity; Sewage